Potential of dimethyl ether as an additive in CO2 for shale oil recovery. (15th July 2021) - Kong, Shaoqi; Feng, Gan; Liu, Yueliang; Li, Kunjie
Graphical abstract: Highlights: Dimethyl ether decreases the interfacial tension of CO2 -shale oil mixtures more significantly. Oil viscosity is more decreased with the addition of dimethyl ether. CO2 injection with the assistance of dimethyl ether is more efficient in recovering shale oil from the smaller pores. Abstract: CO2 injection has been recently proposed as an efficient method for oil recovery from shale reservoirs. However, significant amount of shale oil is still remaining in oil reservoirs after CO2 performance due to the reservoir heterogeneity and extremely low permeability. In this work, dimethyl ether is adopted as an additive in CO2 for enhancing shale oil recovery. The effect of dimethyl ether on the interfacial tension and viscosity of shale oil-CO2 systems are first measured. Using the low-field nuclear magnetic resonance (LFNMR) technique, dimethyl ether assisted CO2 injection is implemented on oil-saturated core samples to evaluate the performance of dimethyl ether as an additive in CO2 for shale oil extraction. Test results show that dimethyl ether decreases the interfacial tension of CO2 -shale oil system more significantly compared to the traditional solvents, i.e., propane and n -butane. In addition, oil viscosity is more decreased when dimethyl ether is added. Based on the LFNMR tests, CO2 injection with the assistance of dimethyl ether is more efficient in recovering shale oil from the smaller pores, which is much higher than the traditional flooding scenarios, i.e., propane and n -butane assisted CO2 injection; dimethyl ether benefits to the solubility of CO2 in shale oil, which decreases the interfacial tension between CO2 and the in-situ oil and reduces oil viscosity at the same time. It enables a much higher shale oil recovery from the smaller pores. This study is expected to inspire new strategies that can be applied for shale oil reservoir development by adding cosolvents as an additive to CO2 for assisting CO2 injection.